Eating Disorders in Evidence. Evidence-Based Clinical Compendium on Eating and Food Ingestion Disorders - Analía Verónica Losada (Perspectivas Metodológicas​)
A detailed text on Eating Disorders is presented here, covering their origins, etiology, epidemiology, classification, and treatment. The work is completed by the presentation of clinical cases.